2021
DOI: 10.1136/openhrt-2020-001565
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of latest viscoelastic coagulation assays in the transcatheter aortic valve implantation setting

Abstract: BackgroundPoint of care viscoelastic measures with thromboelastography (TEG; Haemonetics Corporation, Switzerland) and thromboelastometry (ROTEM, Tem Innovations GmbH, Germany) now supersede laboratory assays in the perioperative assessment and management of coagulation. To the best of our knowledge, this sophisticated coagulation assessment has not been performed to characterise thrombotic changes in the transcatheter aortic valve implantation (TAVI) setting, nor have the two latest iteration cartridge-based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Finally, concerning maximum clot strength MA HKH , previous studies have shown that the MA HKH value transiently increases immediately after TAVI and normalises 6 hours postoperatively. 8 The present results show that MA HKH decreases from POD 1 to POD 3, indicating an antithrombotic change that may have resulted from a stronger effect of decreased platelet function than increased coagulation capacity after TAVI. These results may suggest that patients are more at risk for bleeding than for thromboembolism in the immediate post-TAVI period.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Finally, concerning maximum clot strength MA HKH , previous studies have shown that the MA HKH value transiently increases immediately after TAVI and normalises 6 hours postoperatively. 8 The present results show that MA HKH decreases from POD 1 to POD 3, indicating an antithrombotic change that may have resulted from a stronger effect of decreased platelet function than increased coagulation capacity after TAVI. These results may suggest that patients are more at risk for bleeding than for thromboembolism in the immediate post-TAVI period.…”
Section: Discussionmentioning
confidence: 48%
“…Only a few studies have examined changes in coagulation and platelet function using TEG after TAVI. Although previous studies using TEG 6s have reported intraprocedural thrombophilic tendency after valve implantation in TAVI, 8 there have been no studies after postoperative day (POD) 1. In addition, the trend of platelet function has not yet been adequately studied, particularly with TEG 6s.…”
Section: Introductionmentioning
confidence: 99%
“…TEG measures the speed and strength of coagulation, and provides a rapid global assessment of hemostatic function, including the parameters R (time until clot formation starts), K (rate of clot formation), and MA (maximum clot strength) 16 . The TEG 6s PlateletMapping cartridge has four channels: kaolin/heparinase (HKH), reptilase/factor XIIIa/abciximab (ActF), ADP/ActF (ADP) and arachidonic acid/ActF (AA) 17 . Seven parameters were measured: R‐HKH, K‐HKH, and MA‐HKH, which are the R, K, and MA values measured using HKH; MA‐ActF, the MA value measured using ActF; MA‐HKH minus MA‐ActF, the difference between MA values measured using HKH and ActF; and Aggregation‐ADP and MA‐ADP, the aggregation rate and MA measured using ADP.…”
Section: Methodsmentioning
confidence: 99%
“…16 The TEG 6s PlateletMapping cartridge has four channels: kaolin/heparinase (HKH), reptilase/factor XIIIa/abciximab (ActF), ADP/ActF (ADP) and arachidonic acid/ActF (AA). 17 Seven parameters were measured: R-HKH, K-HKH, and MA-HKH, which are the R, K, and MA values measured using HKH; MA-ActF, the MA value measured using ActF; MA-HKH minus MA-ActF, the difference between MA values measured using HKH and ActF; and Aggregation-ADP and MA-ADP, the aggregation rate and MA measured using ADP.…”
Section: Tegmentioning
confidence: 99%
“… 75 76 A similar study of patients in China, using the TEG PlateletMapping Assay to stratify presurgical timing for patients on DAPT, also showed a reduced waiting time to 3.2 days prior to coronary artery bypass grafting, with no statistically significant difference in blood transfusions during surgery. 66 …”
Section: Left Atrial Appendage Closurementioning
confidence: 99%